High-quality genome sequence of white lupin provides insight into soil exploration and seed quality - Bárbara Hufnagel (Nature Portfolio, 2020)
White lupin is an annual crop cultivated for protein rich seeds and can produce cluster roots for efficient phosphate acquisition. Here, the authors generate high quality genome assemblies of a cultivated accession, a landrace, and a wild relative and provides insight into soil exploration and seed quality.